Accession, Property Acquisition, and Libertarianism (Diametros, 2025)
In the present paper we argue that besides four traditional methods of property acquisition – that is, homesteading, production, voluntary transfer and rectification of injustice – libertarianism also recognizes a fifth method, namely the method of accession. We contend that not only have some libertarian scholars implicitly embraced the accession principle, but also that if libertarianism wants to distribute exclusive ownership to indivisible things produced from inputs supplied by two or more parties without running into conflict with its own principles of justice, it has to recognize accession as the fifth mode of appropriation. As the main thesis of the paper goes against the received view concerning the very core of libertarianism, that is, its methods of property acquisition, the text indicates some new developments within the libertarian theory of justice.
Keywords: accession; property acquisition; rights; justice; libertarianism